A molecular view of the role of chirality in charge-driven polypeptide complexation1. Issue 8 (28th February 2015) - Hoffmann, K. Q.; Perry, S. L.; Leon, L.; Priftis, D.; Tirrell, M.; de Pablo, J. J.
<x xml:space="preserve">Abstract</x> Atomistic simulations show how changes in the backbone chirality of peptides can control the formation of coacervate versus precipitate phases.